“SWEET PAPAYA SEED CANDY” ANTIBACTERIAL ESCHERICHIA COLI CANDYWITH PAPAYA SEED (CARICA PAPAYA L.) - Tika Pangesti; Ika Nur Fitriani; Firdiawan Ekaputra; Andi Hermawan (Pelita - Jurnal Penelitian Mahasiswa UNY, 2013)
This research is experimental research aims to knowing how to made papayaseed candy as antibacterial in Escherichia coli and knowing inhibition zone of sweetpapaya seed candy against bacteria E. coli. This research give alternative new productof healthy food and improve economic value of papaya seed (Carica papaya L.)The process in this research has for ways: making papaya seed powder, makingjelly candy, making solution candy, and testing the bacterial growth inhibition zone ofEscherichia coli bacteria. This proses was held for two days in “Balai LaboratoriumKesehatan Yogyakarta”Result of this research is papaya seed can be processed to made papaya seedcandy by dried and refined. Beside on the bacterial growth inhibition testing, papayaseed candy didn’t have inhibition zone against Escherichia coli bacteria.